Microbial contamination analysis of drinking water from bulk dispensers and fast-food restaurants in the Eastern Coachella Valley, California - Thomas Dama Hile; Stephen G. Dunbar; Ryan G. Sinclair (Water Supply, 2023)
Safe drinking water is a fundamental requirement for human life. The deterioration of water quality primarily involves microbiological hazards, since most evident water-related health problems are the result of microbial contamination. The aim of this study was to evaluate the microbial contamination of drinking water from three sources: water vending machines (WVMs), soda fountains (SFs), and tap water (TW) in the Eastern Coachella Valley (ECV) using physico-chemical parameters, conventional cultivable methods, including IDEXX technology and molecular methods. A total of 72 samples were analyzed and results indicated heterotrophic plate counts (HPCs) bacteria in 20% of samples from WVMs, 25% of samples from SFs, 33.3% of TW samples, and 76% of swab samples. Results also demonstrated 20% of WVM, 88% of swab samples, 41% of SF, and 50% of TW samples had total coliforms. Our qPCR indicated the presence of genetic materials of all six selected microorganisms (Salmonella spp, Listeria monocytogenes, Pseudomonas aeruginosa, Campylobacter jejuni, Escherichia coli, Enterococcus faecalis) used as indicators of pathogenic microorganisms in water from WVMs, SFs, and TW, and were represented at different concentrations and predominance. HIGHLIGHTS First study in the Eastern Coachella Valley to assess the water quality from soda fountains, water vending machines, swabs, and tap water.; This study reinforces the health risk of biofilms in water dispensers and the importance to develop surveillance and regulation that target water dispensers.; The study coupled physico-chemical parameters, DEXX Quanti-Trays, HPC, and qPCR.;